The Influence of Work Culture, Ability and Commitment to the Performance of the Office of the National Land Agency of Labuhan Batu Regency - Anwar Siregar; Elvina Elvina; Abd. Halim (Budapest International Research and Critics University, 2022)
The role of human resources as an institutional driver in achieving goals must be in accordance with the work achieved. Efforts to develop this goal can be done by developing a work culture, ability and commitment so that employee performance can be realized. This study aims to analyze the influence of work culture, ability and commitment on the performance of the employees of the National Land Agency Office of Labuhanbatu Regency. This type of research is quantitative with data collection techniques used are observation, documentation and questionnaires. The population in this study were 119 employees of the National Land Agency Office of Labuhanbatu Regency. The research sample was taken using the slovin formula, with a total of 92 person. The analysis used in this research is multiple linear regression. The multiple linear regression equation obtained in this study is: Y=1.031+0.203X1+0.557X2 +0.448X3. The coefficient value on Work Culture is 0.203, Ability is 0.557 and Commitment is 0.448, with a constant value of 1.031. The results of the partial test with a t-count value of 2.337 > t-table 1.6623 indicate thatwork culture (X1) has a positive and significant effect on employee performance variables (Y). Then the value of t arithmetic is 3.498 > t table 1.6623 explains that ability (X2) has a positive effect on employee performance variable (Y). Furthermore, the t-count value of 4.176 > t table 1.6623 can be interpreted that commitment (X3) has a positive effect on the employee performance variable (Y). Simultaneous test results with the value of Fcount is 71.667> Ftable 2.71 and a significance value of 0.000 <0.05. The results of this study conclude that Work Culture (X1), Ability (X2) and Commitment (X3) simultaneously have a positive and significant effect on employee performance (Y). The value of R Square from the analysis of the coefficient of determination of 0.588 means that Employee Performance (Y) can be explained by the variables of Work Culture (X1), Ability (X2) and Commitment (X3) of 71%, while the remaining 29% can be explained by other variables that do not investigated in this study.